2015
DOI: 10.1186/s12947-015-0005-8
|View full text |Cite
|
Sign up to set email alerts
|

The use of strain, strain rate, and displacement by 2D speckle tracking for assessment of systolic left ventricular function in goats: applicability and influence of general anesthesia

Abstract: BackgroundAssessment of left ventricular (LV) systolic function can be achieved by conventional echocardiographic methods, but quantification of contractility, regional myocardial function, and ventricular synchrony is challenging. The goal of this study was to investigate the applicability of two-dimensional speckle tracking (2DST) to characterize segmental and global wall motion for assessment of LV function and LV synchrony in healthy goats. We aimed to describe the techniques, report normal values of a var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 31 publications
5
15
0
Order By: Relevance
“…Another major limitation of the study was the choice of recorded image orientation for 2DST analysis. Analyses were performed only on short axis views of the LV, while short axis and long axis views were used in humans, dogs, horses and in the previous study in goats [3,20,23,29,36]. In humans, the apical 4-chambers long axis view is often used for colour flow and pulsed wave Doppler echocardiography, for tissue Doppler imaging, and for acquisition of myocardial longitudinal strain [2,36].…”
Section: Observation Of An Exercise Effect On 2dst Values In Goats Comentioning
confidence: 99%
“…Another major limitation of the study was the choice of recorded image orientation for 2DST analysis. Analyses were performed only on short axis views of the LV, while short axis and long axis views were used in humans, dogs, horses and in the previous study in goats [3,20,23,29,36]. In humans, the apical 4-chambers long axis view is often used for colour flow and pulsed wave Doppler echocardiography, for tissue Doppler imaging, and for acquisition of myocardial longitudinal strain [2,36].…”
Section: Observation Of An Exercise Effect On 2dst Values In Goats Comentioning
confidence: 99%
“…The use of 2DST has been described in several domestic animals species such as dogs [14], horses [15,16], pigs [17], sheep [18], calves [19] and goats [20]. This technique has been recommended to assess LV function in small animals with several cardiac diseases, like chronic mitral valve regurgitation in dogs [21].…”
mentioning
confidence: 99%
“…In horses, this technique was successfully applied to detect myocardial injuries occurring with various myopathies [22,23]. In goats, the 2DST technique has been demonstrated to be feasible in standing position and under general anaesthesia [20] but, to the best of the authors' knowledge, neither repeatability studies of the technique, nor 2DST measurements in 4 exercising animals or in animals with cardiac disease have been reported in goats.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is also valuable in cardiac resynchronization therapy (D'Andrea et al, 2007;Shi et al, 2009), diagnosis of arrhythmogenic right ventricular cardiomyopathy (Teske et al, 2009) and other systemic diseases secondarily affecting right heart function (Kosmala et al, 2007;Lindqvist et al, 2006;Matias et al, 2009). In veterinary medicine, speckle tracking has been used so far to evaluate left ventricular function in dogs (Chetboul et al, 2007b), horses (Schwarzwald et al, 2009a) and goats (Berli et al, 2015). In dogs, it was shown that the left ventricular contractility is impaired and the speckle tracking parameters were changed in dogs with cardiomyopathy (Chetboul et al, 2007a).…”
mentioning
confidence: 99%